Developing STREAM (Science, Technology, Religiosity, Engineering, Art, and Mathematics) Based Tiktok Video on Buffer Solution Lesson - Dwi Riva Arianti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
This research was instigated by the lack of learning media used repeatedly outside class hours. This research aimed at producing STREAM (Science, Technology, Religiosity, Engineering, Art, and Mathematics) based Tiktok video learning media on Buffer Solution lesson that was tested its validity based on material and media expert validation, teacher and student practicality test. It was Research and Development (R&D) with 4-D (Define, Design, Development, Disseminate) development model. This research was administered at State Senior High School 1 Merbau, Merbau District, Kepulauan Meranti Regency. The subjects of this research were material experts, media experts, teachers, and the eleventh-grade students of MIA1. The object was STREAM based Tiktok video learning media on Buffer Solution lesson. The result of validation by material experts showed the percentage 90.278% with very valid criterion, and the percentage by media experts was 95% with very valid criterion. Teacher practicality test showed the percentage 98.4375% with very practical criterion, and student response practicality test showed the percentage 91.319% with very practical criterion. Based on these findings, it could be concluded that STREAM based Tiktok video learning media on Buffer Solution lesson was appropriate to be used as a learning medium in the learning process.